Producing the planar multiphoton sources by photonuclear technique: 2. Experimental study - Dikiy, N.P.; Lyashko, Yu.V.; Uvarov, V.L. (Вопросы атомной науки и техники, 2016)
Characteristics of the two-and three-photon sources are analyzed by gamma-ray spectrometric method. The sources are obtained by combining the inactive foils from indium, tantalum, tungsten and lead with planar -sources on the basis of the isotopes ⁵⁷Со and ¹⁷⁹Та. The -sources are produced by activating the foils from nickel and tantalum in the bremsstrahlung field of an electron accelerator. The possibility to control the number, energy and intensity of the spectral bands of a combined source by selecting the material, thickness, order of arrangement and quantity of its components is demonstrated. The experimental results on band intensity of the sources under study are satisfactory agreed with the data calculated on the basis of a developed analytical model Методом гамма-спектрометрического анализа исследованы характеристики двух- и трехфотонных источников, полученных путѐм комбинации неактивных фольг из индия, тантала, вольфрама и свинца с планарными -источниками на основе изотопов ⁵⁷Со и ¹⁷⁹Та. Последние произведены путѐм активации фольг из никеля и тантала в поле тормозного излучения ускорителя электронов. Показана возможность регулирования числа, энергии и интенсивности спектральных полос источников с помощью выбора материала, толщины, порядка расположения и количества их компонентов. Результаты измерения интенсивности полос излучения исследованных источников удовлетворительно согласуются с расчѐтными данными на основе разработанной аналитической модели. Методом гамма-спектрометричного аналізу досліджено характеристики двох та трьохфотонних джерел, що одержані шляхом комбінації неактивних фольг з індію, танталу, вольфраму та свинцю з планарними -джерелами на основі ізотопів ⁵⁷Со та ¹⁷⁹Та. Останні вироблені шляхом активації фольг з нікелю та танталу в полі гальмівного випромінювання прискорювача електронів. Показана можливість регулювання числа, енергії та інтенсивності спектральних смуг джерел за допомогою вибору матеріалу, товщини, порядку розміщення і кількості їх компонентів. Результати вимірювання інтенсивності смуг випромінювання досліджуваних джерел задовільно узгоджуються з даними розрахунків на основі розробленої аналітичної моделі.